Will Telework Reduce Travel? An Evaluation of Empirical Evidence with Meta-Analysis - Laísa Braga Kappler; Rui Colaço; Patrícia C. Melo; João de Abreu e Silva (Urban Science)
Telework emerged in the 1970s with the advent of Information and Communication Technologies (ICT) as a potential substitute for commuting trips and an answer to avoid congestion. While early studies supported this substitution effect, subsequent research has presented contradictory findings, with some studies demonstrating complementary effects and increased travel distances, while others show a reduction in travel or mixed results. These discrepancies may arise from methodological differences in study design, sampling, and modeling approaches. To analyze these factors, a systematic literature review complemented by three meta-analyses was developed. OLS and GLS-RE models were built to measure telework impacts on the number of trips (total and by purpose), commuting distance, and total distance traveled. Our research suggests that while telework reduces commuting and business trips, particularly for full-time teleworkers, it may increase commuting distances. Total distance traveled presents mixed results, heavily dependent on research design. By identifying these patterns, we outline methodological directions for future research, including improved sampling strategies, advanced modeling techniques, and rigorous control variable selection.